Gender and the professions
1 online resource
Keywords: "This book examines gender and professions in the 21st century. Historically the professions encompassed law, medicine and the church, all of which excluded women from participation. Industry and the 20th century introduced new professions such as engineering and latterly information technology skill and, whilst the increase in credentialism and accreditations open up further avenues for professions to develop, many of the 'newer' professions exhibit similar gendered characteristics, still based on a perceived masculine identity of the professional workers and the association of the professional with high level credentials based on university qualifications. In contrast, professions such as teaching and nursing, characterized as women's professions which reflected women's socially acceptable role of caring, developed as regulated occupations from the late 19th century. Since the 1970s and the women's movements, anti-discrimination and equal opportunity legislation and policies have aimed to break down the gendered bastion of the professions and grant women entry. With growing numbers of women employed in a range of professions and the political importance of gender equality gaining prominence globally, Gender and the Professions also considers how women and men are faring in a diverse range of professional occupations. Aimed at researchers, academics and policy makers in the fields of Professions, Gender Studies, Organizational Studies and related disciplines. Gender and the Professions provides new insights of women's experiences in the professions in both developed and less developed countries and in professions less often explored. "--Provided by publisher.